PENGARUH PENERAPAN BRIMO TERHADAP PENINGKATAN KUALITAS LAYANAN DAN KEPUASAN NASABAH BANK BRI - Rizha Desty Septia; Jeni Putriani; Miki Rinaldo; Indi Ramadani; Hendri Hendri (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The rapid development of digital technology has encouraged the banking industry to transform its services in order to improve service quality and customer satisfaction. One of the digital banking innovations developed by Bank Rakyat Indonesia (BRI) is BRImo as a mobile banking application. This study aims to analyze the effect of the implementation of BRImo on improving service quality and customer satisfaction at Bank BRI. This research employs a quantitative method with a survey approach. Data were collected through the distribution of questionnaires to BRI customers who actively use the BRImo application for banking transactions. The data were analyzed using multiple linear regression analysis to examine the effect of BRImo implementation on service quality and customer satisfaction. The results indicate that the implementation of BRImo has a positive and significant effect on improving the service quality of Bank BRI. Furthermore, improved service quality through the use of BRImo also has a positive impact on customer satisfaction. These findings suggest that the digitalization of banking services through the BRImo application enhances service effectiveness by providing convenience, speed, and security for customers. Therefore, Bank BRI is expected to continuously improve BRImo features and security systems to maintain and increase customer satisfaction in the long term.